Homozygous deletions within human chromosome band 9p21 in melanoma. - Fountain, J W (1992)
Genetic studies have implicated the early involvement of a gene on chromosome arm 9p in the development of cutaneous melanoma. We have performed loss-of-heterozygosity studies to confirm these original findings and identify the most frequently rearranged or deleted region of 9p. Eight markers were analyzed, including (from 9pter to proximal 9q) D9S33, the beta-interferon (IFNB1) locus, the alpha-interferon (IFNA) gene cluster, D9S126, D9S3, D9S19, the glycoprotein 4 beta-galactosyltransferase (GGTB2) gene, and the argininosuccinate synthetase pseudogene 3 (ASSP3). Two or more of these loci were found to be hemizygously reduced in 12 of 14 (86%) informative metastatic melanoma tumor and cell line DNAs, and homozygous deletions of the marker D9S126 were observed in 2 of 20 (10%) melanoma cell lines. These findings have resulted in the identification of a small critical region of 2-3 megabases on 9p21 in which a putative melanoma tumor-suppressor gene appears likely to reside. Several 9p candidate genes, including IFNB1, the IFNA gene cluster, GGTB2, and the tyrosinase-related protein (TYRP) locus, have all been eliminated as potential targets because they are located outside of the homozygously deleted regions.